Storm - MacHale, D. J. (MacHale, D. J. SYLO chronicles, 2014)
Having escaped from Pemberwick Island, Kent, Tori, Olivia, and Tucker continue to try to get word out about SYLO, the organization that had quarantined them, while trying to avoid being caught in the middle of an inexplicable new civil war.